Support workers knowledge, skills and education relating to dementia – a national survey [version 2; peer review: 1 approved, 2 approved with reservations] - Victoria A Goodwin; Richard Griffin; Fay Manning; Abigail J Hall (NIHR Open Research)
Background Dementia affects over 55 million people globally, projected to double by 2050. In the UK, non-registered staff, including healthcare assistants (HCAs) and clinical support workers, provide a significant portion of dementia care, yet receive limited training. This study explores the knowledge, training, and attitudes of support workers towards dementia. Methods A cross-sectional web-based survey was conducted from February 1 to April 1, 2024, targeting support workers in England. The survey included demographic information, dementia knowledge (using the Dementia Knowledge Assessment Scale, DKAS), and attitudes (using the Dementia Attitudes Scale, DAS). Data were analysed using descriptive statistics, ANOVA, t-tests, and Pearson’s correlation. Results One hundred and nine support workers responded, predominantly female (90%) and white British (76.4%), from various NHS settings and occupational groups. The majority (79.8%) had received dementia training, primarily from their organisations. Challenges included managing behavioural and psychological symptoms and communication difficulties. There was no significant correlation between years of experience and dementia knowledge (r = -0.019) or attitudes (r = -0.057). However, higher occupational grades were associated with greater dementia knowledge (p = <0.01). A moderate positive correlation was found between dementia knowledge and attitudes (r = 0.35, p = <0.01). Despite high levels of knowledge, support workers often feel inadequately prepared to provide optimal dementia care, indicating a need for more comprehensive training. Challenges in communication and managing symptoms highlight areas for improvement. The study suggests that better training can improve both knowledge and attitudes, enhancing care quality for people living with dementia. Conclusion Support workers play a crucial role in dementia care but require more robust training programs to meet the growing demands. Enhanced training can improve their knowledge and attitudes, leading to better care outcomes for people with dementia.